Identification of a potential functional single nucleotide polymorphism for fatness and growth traits in the 3'-untranslated region of the PCSK1 gene in chickens - Zhang, K; Cheng, B H; Yang, L L; Wang, Z P; Zhang, H L; Xu, S S; Wang, S Z; Wang, Y X; Zhang, H; Li, H (Journal of animal science, 2017)
Prohormone convertase 1/3 is a serine endoprotease belonging to the subtilisin-like proprotein convertase family that is encoded by the () gene, and its major function is the processing and bioactivation of the proproteins of many kinds of neuroendocrine hormones, including insulin, cholecystokinin, and adrenocorticotropic hormone. The results of our previous genomewide association study indicated that the gene might be an important candidate gene for fatness traits in chickens. The objectives of this study were to investigate the tissue expression profiles of gene and to identify functional variants associated with fatness and growth traits in the chicken. The results indicated that mRNA was widely expressed in various tissues, especially neuroendocrine and intestinal tissues. Of these 2 tissue types, mRNA expression in lean males was significantly higher than in fat males. A SNP in the 3' untranslated region of (c.*900G > A) was identified. Association analysis in the Arbor Acres commercial broiler population and Northeast Agricultural University broiler lines divergently selected for abdominal fat content (NEAUHLF) population showed that the SNP c.*900G > A was associated with abdominal fat weight, abdominal fat percentage, BW, metatarsus length, and metatarsal circumference. In the 5th to 19th generation (G to G) of NEAUHLF, the allele frequency of c.*900G > A changed along with selection for abdominal fat content. At G, allele G of c.*900G > A was predominate in the lean line, whereas allele A was predominate in the fat line. Functional analysis demonstrated that allele A of c.*900G > A reduced mRNA stability and consequently downregulated gene expression. These results suggested that c.*900G > A was a functional SNP for fatness and growth traits in the chicken. The results of this study provide basic molecular information for the role of gene in avian growth and development, especially obesity.